Estrogen receptor β ligand therapy activates PI3K/Akt/mTOR signaling in oligodendrocytes and promotes remyelination in a mouse model of multiple sclerosis - Shalini Kumar; Rhusheet Patel; Spencer Moore; Daniel K. Crawford; Nirut Suwanna; Mario Mangiardi; Seema K. Tiwari-Woodruff (Neurobiology of Disease, 2013)
The identification of a drug that stimulates endogenous myelination and spares axon degeneration during multiple sclerosis (MS) could potentially reduce the rate of disease progression. Using experimental autoimmune encephalomyelitis (EAE), a mouse model of MS, we have previously shown that prophylactic administration of the estrogen receptor (ER) β ligand 2,3-bis(4-hydroxyphenyl)-propionitrile (DPN) decreases clinical disease, is neuroprotective, stimulates endogenous myelination, and improves axon conduction without altering peripheral cytokine production or reducing central nervous system (CNS) inflammation. Here, we assessed the effects of therapeutic DPN treatment during peak EAE disease, which represents a more clinically relevant treatment paradigm. In addition, we investigated the mechanism of action of DPN treatment-induced recovery during EAE. Given that prophylactic and therapeutic treatments with DPN during EAE improved remyelination-induced axon conduction, and that ER (α and β) and membrane (m)ERs are present on oligodendrocyte lineage cells, a direct effect of treatment on oligodendrocytes is likely. DPN treatment of EAE animals resulted in phosphorylated ERβ and activated the phosphatidylinositol 3-kinase (PI3K)/serine–threonine-specific protein kinase (Akt)/mammalian target of rapamycin (mTOR) signaling pathway, a pathway required for oligodendrocyte survival and axon myelination. These results, along with our previous studies of prophylactic DPN treatment, make DPN and similar ERβ ligands immediate and favorable therapeutic candidates for demyelinating disease.